Pharmacokinetics and immunogenicity of a recombinant human butyrylcholinesterase bioscavenger in macaques following intravenous and pulmonary delivery. (5th December 2015) - Rosenberg, Yvonne J.; Adams, Robert J.; Hernandez-Abanto, Segundo; Jiang, Xiaoming; Sun, Wei; Mao, Lingjun; Lee, K. David
Abstract: Recombinant (r) and native butyrylcholinesterse (BChE) are potent bioscavengers of organophosphates (OPs) such as nerve agents and pesticides and are undergoing development as antidotal treatments for OP-induced toxicity. Because of the lethal properties of such agents, regulatory approval will require extensive testing under the Animal Rule. However, human (Hu) glycoprotein biologicals, such as BChE, present a challenge for assessing immunogenicity and efficacy in heterologous animal models since any immune responses to the small species differences in amino acids or glycans between the host and biologic may alter pharmacodynamics and preclude accurate efficacy testing; possibly underestimating their potential protective value in humans. To establish accurate pharmacokinetic and efficacy data, an homologous animal model has been developed in which native and PEGylated forms of CHO-derived rMaBChE were multiply injected into homologous macaques with no induction of antibody. These now serve as controls for assessing the pharmacokinetics and immunogenicity in macaques of multiple administrations of PEGylated and unmodified human rBChE (rHuBChE) by both intravenous (IV) and pulmonary routes. The results indicate that, except for maximal concentration (Cmax), the pharmacokinetic parameters following IV injection with heterologous PEG-rHuBChE were greatly reduced even after the first injection compared with homologous PEG-rMaBChE. Anti-HuBChE antibody responses were induced in all monkeys after the second and third administrations regardless of the route of delivery; impacting rates of clearance and usually resulting in reduced endogenous MaBChE activity. These data highlight the difficulties inherent in assessing pharmacokinetics and immunogenicity in animal models, but bode well for the efficacy and safety of rHuBChE pretreatments in homologous humans. Highlights: Parallel tests in homologous systems is required for assessing efficacy of rHuBChE. Plasma clearance of intravenous PEG-rHuBChE is more rapid than PEG-rMaBChE. PEG-rHuBChE, but not PEG-rMaBChE, is immunogenic in macaques. Anti-HuBChE antibodies clear endogenous MaBChE as well as exogenous PEG-rHuBChE. An antibody independent mechanism for clearance of BChE appears to exist.